Effects of stand age on litter quality, decomposition rate and nutrient release of Kazdagi fir (Abies nordmanniana subsp. equi-trojani) - Savaci, Gamze; Sarıyıldız, Temel (Sisef-Soc Italiana Selvicoltura Ecol Forestale, 2020)
The influence of stand age on litter quality, decomposition rate and nutrient release was examined in pure stands of Kazdagi fir (Abies nordmanniana subsp. equi-trojani [Steven] Spach) differing in age (Fir(38), Fir(60), Fir(90) and Fir(100) years). The needle litters were collected and analysed for initial total carbon, cellulose, hemicellulose, lignin and nutrient concentrations (N, P, K, Ca, S, Mg, Mn and Fe). Initial litter quality parameters varied significantly among the four stand age classes. The Fir(60) and Fir(100) stands had higher total C than the Fir(38) and Fir(90) stands, while the Fir38 and Fir(100) stands had higher N than the Fir(60) and Fir(90) stands. Mean cellulose and hemicellulose concentrations were highest in the Fir(90) stand, while mean lignin concentration was highest in the Fir38 stand. Fir(90) stand showed the highest ratios of C/N and Lignin/N. In general, the older fir stands showed higher Ca, Mg and K concentrations and lower P and S concentrations than the younger stands. The litter, however, showed higher a Mn concentration under the Fir(60). Mean Fe concentration was highest under the Fir(38) stand and lowest under the Fir(60) stand. Litter decomposition was studied in the field using the litterbag technique. The litterbags were placed on the soil under each stand age class and sampled every 6 months for 2 years. The interaction of stand age and time on the mass loss was significant (p<0.01). The repeated measures ANOVA showed that the main effect of time on the mass loss was also significant (p<0.001). Needle litters under Fir(100) and Fir(60) stands decomposed faster than the needle litters under Fir(90) and Fir(38) stands. The calculated times required for 50% mass loss were higher under Fir(38) (1.35 y) and Fir(90) (1.27 y) stands than under Fir(100) (1.05 y) and Fir(60) (1.06 y) stands. The litters in Fir(38) and Fir(90) stands need approximately 4 years for 95% mass loss compared to the litters in Fir(60) and Fir(100) stands, which need 3 years. In general, Ca, Mg and S concentrations increased over time, whereas K and Mn decreased. These results illustrate that stand age is a key factor to be considered when studying litter decomposition dynamics.
Keywords: Litter Quality; Stand Age; Litter Decomposition; Nutrient Release; Fir